2021
DOI: 10.7441/joc.2021.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Intermediary Role of Relationship Ending Capability and Dark Side Between Network Embeddedness and SMEs’ Innovation Performance

Abstract: A key driver of firm competitive advantage is the firm’s ability to develop along with the everchanging business environment and associated market demands by being innovative. Small and medium-sized enterprises (SMEs), however, often lack adequate resources to develop innovation, so they search for external resources to augment the deficiency of their internal resources. Network embeddedness has many advantages for the firm, but it also has a dark side which has a negative effect on the network relationship. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In the vein of the above works, acquiring knowledge and resources has been suggested as an effective method for addressing the increasing complexity and uncertainty of the competitive landscape (Díaz-Díaz and de Saá Pérez 2014; Ortiz et al 2018). To improve the flexibility to adapt to environmental changes, it is suggested that firms broaden their knowledge base by acquiring external knowledge from diverse sources (Katila and Ahuja 2002;Teece et al 2016;Tian et al 2021). A number of studies, in fact, have found that the breadth of external knowledge sources, which is the number of external sources exploited to acquire knowledge and resources, is positively associated with performance (Laursen and Salter 2006).…”
Section: Hypothesesmentioning
confidence: 99%
“…In the vein of the above works, acquiring knowledge and resources has been suggested as an effective method for addressing the increasing complexity and uncertainty of the competitive landscape (Díaz-Díaz and de Saá Pérez 2014; Ortiz et al 2018). To improve the flexibility to adapt to environmental changes, it is suggested that firms broaden their knowledge base by acquiring external knowledge from diverse sources (Katila and Ahuja 2002;Teece et al 2016;Tian et al 2021). A number of studies, in fact, have found that the breadth of external knowledge sources, which is the number of external sources exploited to acquire knowledge and resources, is positively associated with performance (Laursen and Salter 2006).…”
Section: Hypothesesmentioning
confidence: 99%
“…For SMEs that are good at using their strengths to compensate for weaknesses, solving resource problems by networking with others will most likely obtain competitive advantages ( Tian et al, 2021 ). Because the VRIO conditions for strategic resources take a long time to develop and are difficult to be understood, let alone copied, by competitors, they are the engine for SMEs’ innovation and development ( Angulo-Ruiza et al, 2018 ; Roostika, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firm competitive advantage is driven by its ability to develop along with the everchanging business environment by being innovative. Companies, particularly small-and medium-sized enterprises (SMEs), often lack adequate resources to develop innovation, so they search for external resources needed in innovation activity [Tian et al, 2021]. According to the contemporary paradigm in economics of innovation, new products are mainly the result of cooperation and interactions between three types of actors forming triple helix model: industry, university, and government [Etzkowitz and Leydesdorff, 1995].…”
Section: Theoretical Backgroundmentioning
confidence: 99%